Evaporation process study through in situ and remote sensing data at Tres Quebradas Salt flat - F. Carmona; R. Rivas; A.M.G. Faramiñán; C. Mancino; M. Bayala; W. Perez (Revista de Teledetección)
The calculation of evaporation (Ev) is a fundamental process on the planning of investment for nonmetallic mining in salt flats. Dispose to reliable estimates of evaporation allows to reduce one of the main uncertainties of the flow models in this type of basin. This paper focuses on the calculation of Ev in the Tres Quebradas salt flat, Catamarca (Argentina), applying Priestley-Taylor model whit satellite data. Study area comprises the Tres Quebradas and Verde lagoons, and a central evaporite zone. Satellite data (CERES and OLI-LandSat 8), meteorological information, brine density measurements, evaporation measurements, and spectral signatures to calculations were used. The lagoons evaporation was estimated and by means of a Class A evaporation pan validated. The evaporation control in evaporite zones also was studied using a phreatic level function. Ev values of 1302 mm year–1 and 1249 mm year–1 for the Tres Quebradas and Verde lagoons were obtained, respectively, similar to Class A evaporation pan values measured. In the case of evaporite zones, an average annual value of 152 mm year–1 was estimated, regulated by the phreatic level. In summary, an average annual of system water loss by evaporation of 1.31±0.32 m3 s–1 was obtained, where more than 80% corresponds to the Tres Quebradas and Verde lagoons, and the rest to the central evaporite zone. The results achieved are consistent and will be used as input data in the numerical flow modeling to the estimation of the lithium brine reserve of the salt flats.